TRIAL OF CRIMINAL OFFENSES BY JURY IN THE UNITED STATES OF AMERICA: PROSPECTS OF BORROWING EXPERIENCE BY UKRAINE - Osadchyi, Ilya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to study the question of Ukraine borrowing the experience of the United States of America in terms of consideration of criminal misdemeanors by a jury. The right to judicial protection and its narrowing by the limited competence of the jury court are mentioned to substantiate the urgency of the problem. The understanding of criminal misdemeanors in Ukraine and the United States of America is considered, and a conclusion is drawn regarding a broader understanding of criminal misdemeanors in the United States. Results: the access of citizens of the United States of America to the jury trial in different states was analyzed. It found that in all 50 states, a jury can try misdemeanor cases, with some states only allowing misdemeanors that carry a prison sentence. Attention is focused on the possibility of a jury trial in the event of significant extrajudicial negative consequences for the accused. On the basis of a comparison of the understanding of criminal misdemeanor and criteria for trial by jury in Ukraine and the United States, it was concluded that the loyalty of the American legislator in the matter of trial of criminal misdemeanor by jury is only partially explained by a different understanding of criminal misdemeanor. The importance of the jury trial in terms of the possible nullification of legal norms that contradict society’s notions of justice is mentioned. Discussion: doubts were expressed about the economic feasibility of the possibility of trial of all criminal cases by a jury. It is proposed to borrow the experience of the United States in the consideration of criminal misdemeanors by a jury with a view to the following features: when making changes to the legislation, it is necessary to take into account other differences in the legal status of the jury in Ukraine and the United States (composition, competence, etc.) and differences in the understanding of criminal misdemeanor; the achievement of the goal must be gradual - the "thresholds" for the consideration of cases by jury courts must be gradually lowered, from serious crimes to criminal misdemeanors; it is not necessary to make the right to a trial by jury absolute, the lower limit of the amount of the fine, the term of imprisonment, as well as taking into account other, extrajudicial consequences for the accused (for example, further inability to find a job, deportation, etc.) are necessary.